(3GdaQGSIs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GdMeO ddg eSJMb GdMeO CeG HYO agPg QSGdI eTJedI Ydi eYGbO bdjdI ef Yde GdaQGSI (B,(3GdcdGe ajg eQJH Ydi ebGdGJ s
(3BNQgG (B:s
(3GdOdjd eCNhP ef LfS GdPcQ ef aNPI dLSekG eeJdFkG afaSI UMjaI gPG GdOdjd eCNhP ef GdCfKj s
(3Vef eLehY , JQJjHgG (B: 23s
(3bGd ai cTa GdXfhfs
(3hgh NdGUI cJGH GQSWh eY RjGOGJ egeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs